Risk of heart failure with human immunodeficiency virus in the absence of prior diagnosis of coronary heart disease. - Butt, Adeel A; Chang, Chung-Chou; Kuller, Lewis; Goetz, Matthew Bidwell; Leaf, David; Rimland, David; Gibert, Cynthia L; Oursler, Krisann K; Rodriguez-Barradas, Maria C; Lim, Joseph; Kazis, Lewis E; Gottlieb, Stephen; et al. (Archives of internal medicine, 2011)
Whether human immunodeficiency virus (HIV) infection is a risk factor for heart failure (HF) is not clear. The presence of coronary heart disease and alcohol consumption in this population may confound this association.
Keywords: Adult; Comorbidity; Coronary Disease; Female; Heart Failure; HIV Infections; Humans; Male; Middle Aged; Retrospective Studies; Risk Assessment; Risk Factors; United States; Veterans